A circle has equation x^2+y^2-8x+2y-1=0, the radius of this circle is 3 sqrt 2. x^2+y^2-8x+2y-1=0 x^2-8x+16+y^2+2y+1=1+16+1 (x-4)^2+(y+1)^2=18 The center of the circle is (4, -1) and the radius is sqrt 18 = 3 sqrt 2.

A circle has equation x^2+y^2-8x+2y-1=0, the radius of this circle is 3 sqrt 2. x^2+y^2-8x+2y-1=0 x^2-8x+16+y^2+2y+1=1+16+1 (x-4)^2+(y+1)^2=18 The center of the circle is (4, -1) and the radius is sqrt 18 = 3 sqrt 2.

Added 7/23/2014 3:14:02 AM

This answer has been confirmed as correct and helpful.

There are no comments.